2016
DOI: 10.1007/s00213-016-4452-1
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone attenuates the opioid withdrawal and vulnerability to relapse to heroin seeking in rodents

Abstract: These findings provide new insights on the role of PPARγ on opioid dependence and suggest that pioglitazone may be useful for the treatment of opioid withdrawal in opioid-addicted individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…PPARγ receptor activation by PIO was found to significantly reduce alcohol/ethanol consumption, and relapse to alcohol seeking (Ferguson et al, 2014; Stopponi et al, 2011; Stopponi et al, 2013). Other rodent work has found similarly promising results with opioids, cocaine and methamphetamine (Ciccocioppo et al, 2012; de Guglielmo et al, 2017; Maeda et al, 2007; Miller, 2016). Concerning preclinical findings with nicotine, PPAR alpha agonists have been found to block nicotine reward and induced reinstatement of drug seeking (Mascia et al, 2011; Panlilio et al, 2012).…”
Section: Introductionmentioning
confidence: 74%
“…PPARγ receptor activation by PIO was found to significantly reduce alcohol/ethanol consumption, and relapse to alcohol seeking (Ferguson et al, 2014; Stopponi et al, 2011; Stopponi et al, 2013). Other rodent work has found similarly promising results with opioids, cocaine and methamphetamine (Ciccocioppo et al, 2012; de Guglielmo et al, 2017; Maeda et al, 2007; Miller, 2016). Concerning preclinical findings with nicotine, PPAR alpha agonists have been found to block nicotine reward and induced reinstatement of drug seeking (Mascia et al, 2011; Panlilio et al, 2012).…”
Section: Introductionmentioning
confidence: 74%
“…In this regard, Willcocks and McNally [149] showed that reversible inactivation of dmPFC decreases context-induced reinstatement of alcohol seeking but accelerates acquisition of alcohol self-administration after extinction. Other evidence that suggests that reinstatement and reacquisition of opioid-taking behavior involve dissociable mechanisms is that yohimbine reliably reinstates opioid seeking after extinction [150,151], but has no effect on reacquisition of heroin self-administration [110].…”
Section: Discussionmentioning
confidence: 99%
“…PPARγ is expressed primarily in microglia and PPARγ agonists inhibit the expression of proinflammatory cytokines (Kielian and Drew, 2003). Recent studies show that stimulation of PPARγ reduces heroin self-administration and reinstatement of heroin seeking (de Guglielmo et al, 2016, 2015). …”
Section: Drugs Of Abuse and Glial Cell Activitymentioning
confidence: 99%
“…Interest in PPARγ agonists has grown in many neuroinflammatory disorders due to the expression of PPARγ primarily in microglia and the ability of PPARγ agonists to inhibit the expression of cytokines by monocytes/macrophages and microglia (Kielian and Drew, 2003). In response to the promising preclinical research (de Guglielmo et al, 2016, 2015), researchers sought to test the ability of PIO to alter the abuse potential of opioids in human subjects. One of these trials maintained non-dependent prescription opioid abusers (n=17 completers) on an ascending daily dose of PIO (0 mg, 15 mg, 45 mg) for 2–3 weeks per dose.…”
Section: Drugs Of Abuse and Glial Cell Activitymentioning
confidence: 99%